2017
DOI: 10.2147/ott.s122106
|View full text |Cite
|
Sign up to set email alerts
|

Metronomic treatment of advanced non-small-cell lung cancer with daily oral vinorelbine – a Phase I trial

Abstract: Micro-abstractIn a Phase I dose-finding study of metronomic daily oral vinorelbine in advanced non-small-cell lung cancer, a recommended dose was established for this therapeutic approach. In addition, this trial revealed promising efficacy data and an acceptable tolerability profile. The observed vinorelbine blood concentrations suggest continuous anti-angiogenic coverage.IntroductionWe present a Phase I dose-finding study investigating metronomic daily oral vinorelbine (Navelbine® Oral, NVBo) in advanced non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The first step of the selection process identified fourteen studies that matched the selected MeSH terms (Fig 1). After careful analysis of each publication, four studies were found to be ineligible: the study by Elharrar X et al [14] investigated a mathematical model in a phase I study with various malignant diseases (pharmacological evaluation as primary endpoint); two studies (Rajdev L. et al 2011 and Guetz et al 2017) [15,16] used a daily administration of oral vinorelbine with a “week-on, week-off“schedule; one study was a redundant publication with fewer accrued patients in the first publication 17 than in the final publication (Briasoulis E. et al 2009 [17], n = 14; Briasoulis E. et al 2013, n = 31); finally, one study analyzing 26 patients, and published in mandarin seemed eligible according to the English abstract, albeit retrospective [18]. The authors were contacted in order to test feasibility of including their study in this individual patient-data metaanalysis but could not be reached despite repeated attempts.…”
Section: Resultsmentioning
confidence: 99%
“…The first step of the selection process identified fourteen studies that matched the selected MeSH terms (Fig 1). After careful analysis of each publication, four studies were found to be ineligible: the study by Elharrar X et al [14] investigated a mathematical model in a phase I study with various malignant diseases (pharmacological evaluation as primary endpoint); two studies (Rajdev L. et al 2011 and Guetz et al 2017) [15,16] used a daily administration of oral vinorelbine with a “week-on, week-off“schedule; one study was a redundant publication with fewer accrued patients in the first publication 17 than in the final publication (Briasoulis E. et al 2009 [17], n = 14; Briasoulis E. et al 2013, n = 31); finally, one study analyzing 26 patients, and published in mandarin seemed eligible according to the English abstract, albeit retrospective [18]. The authors were contacted in order to test feasibility of including their study in this individual patient-data metaanalysis but could not be reached despite repeated attempts.…”
Section: Resultsmentioning
confidence: 99%
“…The potential of metronomic chemotherapy has been assessed in various advanced cancer in preclinical and clinical studies. 8 , 12 , 13 , 22 , 23 In metastatic breast cancer, metronomic chemotherapy with vinorelbine is a treatment option. 24 Despite the availability of immunotherapy or targeted therapy agents as first-line treatment in advanced NSCLC, there are still NSCLC patients with advanced disease who may not be eligible for these treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may be important in this challenging population composed of unfit advanced NSCLC patients to explore the use of oral metronomic chemotherapy over standard oral chemotherapy. 22 …”
Section: Discussionmentioning
confidence: 99%
“…The ease of oral VRL administration allows for flexible treatment schedules including a more frequent and metronomic dose application. Various schedules have been evaluated including a fractionated regimen (day 1, 3, 5) and daily intake (Adamo et al 2019;Addeo et al 2010;Guetz et al 2017). In patients with non-small-cell lung cancer, the daily administration of VRL up to 40 mg per day was welltolerated (Banna et al 2018;Guetz et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Various schedules have been evaluated including a fractionated regimen (day 1, 3, 5) and daily intake (Adamo et al 2019;Addeo et al 2010;Guetz et al 2017). In patients with non-small-cell lung cancer, the daily administration of VRL up to 40 mg per day was welltolerated (Banna et al 2018;Guetz et al 2017). For these reasons, VinoMetro aimed to investigate a truly metronomic schedule with daily oral VRL in HR+/HER2− MBC patients following endocrine resistance, by assessing efficacy and safety of doses well below the maximum tolerated dose in advanced breast cancer patients with visceral metastases.…”
Section: Introductionmentioning
confidence: 99%